Phosphorus release characteristics and quantification of microbial population at different stages of phospho-compost production - Mokase, Tsakani Joyce (University of Limpopo, 2016)
This study aimed at assess phosphorus (P) solubility and bioavailability from non-reactive Phalaborwa ground phosphate rock (GPR) using thermophilic co-composting technology. Two types of organic wastes (Cattle, CM and poultry manure, PM) were used to produce different mix ratios (5:5, 7:3, 8:2 and 9:1) of phospho-composts. Control compost of both manures without GPR addition were included. Samples of each compost heap were taken at mesophilic, thermophilic, cooling and maturity stages and used for bioquality and chemical tests. Microbial counts, enzyme activity, molecular analysis, and the quatification of different P forms and fractions were carried out on all compost samples. Results showed that the concentration of P measured in the different phospho-composts differed significantly (p < 0.05). The 8:2 mix ratio gave quantitatively higher P concentration in both CM- and PM-based phospho-composts. Organic P form had the lowest concentration when compared to other P forms and fractions while water soluble-P had the highest concentration as compared to other P fractions. The content of actinomycetes showed correlated positively with EC, phosphatase β-glucosidase, fungi and bacteria but negatively correlated with organic P, Ca-P water P and pH. There was a positive and significant correlation between electrical conductivity, enzyme activity (phosphatase, dehydrogenase and β-glucosidase), fungi, actinomycete and P fractions (Bray P1, Ca-P and Pi value). Acid phosphatase activity correlated negatively with water extractable P, organic P and Ca-P contents but revealed a positively significant correlation with bacteria, fungi and actinomycete counts. Generally higher microbial counts were measured in CM- than PM-based phospho-composts but the concentrations varied with each microbial species. Highest fungi (7.27 CFU g-1) and actinomycete (6.83 CFU g-1) counts were generally recorded in the control composts, which was quantitatively higher in CM- than PM-based phospho-composts. Quantitatively higher enzyme activities were measured across compost types and mix ratios during the cooling phase phospho-compost production; but were statistically comparable to measured values at maturity phase. Acid phosphatase and β-glucosidase enzymes were predominately higher at maturity phase in all cattle manure-based phospho-compost excluding the 5:5 mix ratio. In PM-based phospho-compost, both β-glucosidase and phosphatase were higher at initial phase with PM5:5 , PM9:1 and PM10:0. Dehydrogenase activities were predominately higher at thermophilic and cooling phase from both PM- and CM-based phospho-compost. Results of molecular analysis revealed that Bacillus sp. and Acholeplasma cavigenitalium sp. were dorminant in PM-based phospho-composts while Pseudomonas sp. and Acholeplasma pleciae dorminated the CM-based phospho-composts. In conclusion, results of this study revealed that the type of manure used exerts great influence on the bioquality parameters and the amount of P released. Key words: Phospho-compost, Compost quality, Enzyme activities, Nutrient cycling, Ground phosphate rock, Phosphorus forms and fractions
Thesis (M. Sc. Agriculture (Soil Science)) -- University of Limpopo, 2016
Keywords: Phosphorus; Phosphate rock; Organic wastes; Microbiology; Phosphorus in agriculture